PENERAPAN BAHASA PEMROGRAMAN VISUAL BASIC DALAM PEMBUATAN SISTEM PENDATAAN DIAGNOSA JENIS PENYAKIT DARI HASIL TEST SAMPEL DARAH PADA LABORATORIUM RUMAH SAKIT UMUM DAERAH M. YUNUS BENGKULU - Wahyudi, Jusuf; Utami, Feri Hari (UNIVED Press, 2012)
Computers that have the functionality and usability of diverse basically still in use as a medium of typing, data storage and entertainment. Due to there are computer users who have not been able to streamline the ability of the computer to the maximum.Hospital Laboraturim M. Yunus Bengkulu is one unit for the diagnosis of diseases and always use a computer in completing the work, the current hospital laboratory, M. Yunus Bengkulu in the patient record is manually making it less effective in the data.Based on preliminary described above, the researcher raised about the research data collection application diagnostics of diseases of the results of laboratory tests on blood samples muhammad yunus hospital bengkulu using Visual Basic 6.0.Keywords: Application Diagnosis Disease Type, Visual Basic 6.0.